A high efficiency soft‐switched DC–DC converter with high voltage conversion ratio. (30th December 2020) - Shayeghi, Hossein; Pourjafar, Saeed; Hashemzadeh, Seyed Majid; Blaabjerg, Frede
Summary: This work proposes a kind of DC–DC topology with a higher voltage conversion ratio. The suggested converter utilizes a coupled inductor and a voltage multiplier cell to enhance the voltage conversion ratio. The voltage multiplier cell has the feature of the clamping circuit, which can decrease the maximum voltage of the semiconductors elements. In the presented structure, only one lower ON‐state resistance ( R DS ‐ON ) power switch is utilized that makes the control circuit to be simple. The proposed converter has soft‐switching features such as zero‐current switching (ZCS) and zero voltage switching (ZVS) that lead to decrease the diodes reverse recovery losses and increase the efficiency. Besides, the ripple value of the input current is lower than the other similar works. The high efficiency and low input current ripple make the suggested converter suitable for photovoltaic (PV) applications. In order to approve the technical analysis of the recommended structure, technical investigations and comparison study with some similar structures are carried out. Finally, for demonstrating the advantages of the presented structure, a laboratory circuit is built with 12‐V DC source voltage, 120‐V load voltage, and power rate of 100 W in 50‐kHz operation frequency. Abstract : This paper proposes a new kind of DC–DC converter with a higher voltage conversion ratio. The suggested converter utilizes a coupled inductor and a voltage multiplier cell to enhance the voltage conversion ratio. The voltage multiplier cell has the feature of the clamping circuit, which can decrease the peak voltage through the semiconductors. The proposed converter has soft‐switching features such as zero‐current switching and zero voltage switching that lead to decrease the diodes reverse recovery losses and increase the efficiency.